Legal Analysis of Regional Government Obligations to Provide Burial Land from the Maslahah Mursalah Perspective (Case in Brohol Village, Sei Suka District, Batu Bara Regency - Irawan, Ryan; Tarigan, Tetty Marlina (LEGAL BRIEF, 2025)
This study aims to analyze the government's obligation to provide burial land based on the perspective of positive law in Indonesia and the theory of maslahah mursalah in Islamic law. This study focuses on the case of Brohol Village, Sei Suka District, Batu Bara Regency, which faces the unavailability of burial land due to the lack of attention and active role from the government. The research method used in this study is empirical juridical. The approach used by the researcher is a qualitative approach with descriptive analysis. with primary data collection based on observation and interviews while secondary data is based on literature studies. The results of this study indicate that Brohol Village still does not have land for burial. Based on the Law and the perspective of maslahah mursalah, the Regional Government and Village Government have an obligation to provide burial land used for the Brohol Village community. However, in reality, the government has not yet fulfilled this obligation until the time this research was conducted